Peranan Badan Permusyawaratan Desa Telago - Nuraini Nuraini; Mhd Ansori (Universitas Batanghari Jambi, 2022)
The village government is an inseparable part in the administration of the Republic of Indonesia. The Village Government as the spearhead in the village government system will come into contact and deal directly with the community. The Village Consultative Body functions to accommodate and channel the aspirations of the community. The Village Consultative Body and the Village Government together make a draft village regulation which will be stipulated as a Village Regulation. The filling of the Village Consultative Body members can be processed through direct elections and or through representative deliberation. Based on observations and information obtained by the Telago Village Consultative Body, it has not been going well. This can be seen from the supervisory task of the Village Consultative Body in Telago Village, which seems to be only a formality, because there are complaints about village government administration such as village activities, socialization and lack of communication between communities that are not going well. This paper aims to analyze the role of the Village Consultative Body in the Implementation of Village Government in Telago Village, Keliling Danau District, Kerinci Regency. The type of research used is a sociological juridical research type and uses a socio-legal research approach. Then the sample is determined by purposive sampling, and the data is analyzed qualitatively.